Malaria Multifocal Study Shows the Preference of Orthodox Medicine for Malaria Treatment in Idu, Abuja. - Ezeunala, Mercy N.; Ezaka, Ephraim I.; Margret, Ekpenyong; Izebe, Kasim (British Journal of Healthcare and Medical Research, 2023)
The purpose of this study is to examine the preference for orthodox medicine for malaria treatment among clients attending the Institute of Human Virology center in the National Institute for Pharmaceutical Research and Development (NIPRD), Abuja. To accomplish the purpose of the study, two specific objectives and two corresponding research questions guided the study. A simple random sampling technique was employed to select respondents from the study population majorly focusing on clients who came for their routine health checkups between April and August 2022. 176 clients were randomly selected to participate in the study. Closed-ended questions were used to get accurate and useful information from the respondents. The data collected were analyzed using frequency tables. The findings of this study revealed that insecticides and mosquito nets were mainly used as malaria preventive measures. The majority of the study participants tested positive for malaria infection and among the positive cases, a higher number of them preferred the use of orthodox medicine for treatment.